Serum matrix metalloproteinase-7 levels in infants with cholestasis and biliary atresia - Pejman Rohani; Seyyed Bahador Mirrahimi; Haleh Bashirirad; Parisa Rahmani; Niyoosha Kamran; Hosein Alimadadi; Mahmoud Hajipour; Mohammad Hassan Sohouli (BMC Pediatrics, 2022)
Abstract Background The aim of this study was to evaluate the serum level of matrix metalloproteinase 7 (MMP7) in infants with cholestasis and the diagnostic values of this biomarker to differentiate biliary atresia (BA) from other causes of cholestasis. Methods This multi-center study is conducted during 2 years in Mofid children’s hospital and Children’s Medical Center, Pediatrics Center of Excellence Tehran, Iran. 54 infants with cholestasis were enrolled in this study with a control group consists of 41 healthy infants with the same age. Serum samples were taken from all these patients to assess serum levels of MMP7, Gamma-glutamyl Transferase (GGT). For each biomarker, we calculated the sensitivity and specificity and other statistical characteristics. Results There were 89 subjects, 22 patients with BA, 32 patients with non-BA cholestasis and 41 subjects as control group. The mean serum MMP7 levels in BA, non-BA cholestasis and control group was 15.91 ng/ml ± 6.64, 4.73 ng/ml ± 2.59 and 0.49 ng/ml ± 0.33, respectively. The best cut-off point is calculated 7.8 ng/ml for MMP7 and 434.5 U/L for GGT. The area under curve (AUC) for these two markers are 0.988 ± 0.008 and 0.854 ± 0.052, respectively. The sensitivity and specificity of MMP7 to differentiate biliary atresia from nonbiliary atresia cholestasis in our study was 95.5% and 94.5%, respectively. The sensitivity and specificity of GGT was 77.3% and 77.8%, respectively. These results show that the MMP7 has more sensitivity and specificity in differentiation. Conclusion MMP7 demonstrated good accuracy to differentiate biliary atresia from other causes of cholestasis.